The New Zealand Foreign Policy (2015-2019): Feminist Approach on Global Peacekeeping - Roagaswara, Adrian; Adila, Anisa Nadiya (Andalas Institute of International Studies UNAND, 2021)
Feminism in international relations studies has brought new perspective with its focuses on women’s empowerment and gender equality. The adoption of United Nations Security Council Resolution (UNSCR) 1325 is a starting point of the world's attention on women’s active role in conflict and peace, encouraging UN member countries to participate in promoting Women, Peace, and Security (WPS). New Zealand, as the first self-governing country in the world to allow women suffrage in parliamentary elections, has been committed to promoting the WPS agenda, both in the region and globally. According to the Global Peace Index (GPI), New Zealand became the second most peaceful country in the world in the last few years. With no recent armed conflict and any external threats, New Zealand's National Action Plan (NAP) on the WPS agenda primarily focuses on external affairs. This article seeks to provide an analysis of how feminist values influence New Zealand’s foreign policy on peacekeeping efforts and its implications on global peace. Data shows that during the NAP implementation period (2015-2019), New Zealand has continuous improvement of GPI score, which is a measure of a country's level of peace. New Zealand's efforts to maintain world peace through its aid program to conflict-affected countries also have a relatively positive effect on the level of peace in these countries, as happened in Timor Leste and Papua New Guinea.